An MFDFA Study to find Herd Behaviour and Information Asymmetry during Demonetization - Balasubramanian, Niranjana (Ushus Journal of Business Management, 2021)
The paper attempts to identify how the Indian stock market reacts to an unusual event like demonetization through the observation of herd behavior. The data set considered is the NIFTY 50 index collected on 9th November 2016. This method could become a failure if giant investors are well aware of the massive proceeding as stock markets are prone to information asymmetry. Thus, the existence of the same is checked using Hill estimator. The sectoral herding behavior is also captured for three selective sectors namely PSU banks, Energy sector, and Automobile sector as each sector may pose a different response towards the event. The volatility index is examined for a time period of 10 years from 2008 to 2018.